Single‐center survey of biologic use for inflammatory skin diseases during the coronavirus disease 2019 pandemic. Issue 12 (21st September 2021) - Kado, Soichiro; Kamiya, Koji; Kishimoto, Megumi; Maekawa, Takeo; Kuwahara, Aya; Sugai, Junichi; Komine, Mayumi; Ohtsuki, Mamitaro
Abstract: Coronavirus disease 2019 (COVID‐19) is caused by severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2). The ongoing COVID‐19 pandemic has affected both daily life and medical care; therefore, the aim of this study was to analyze the use of biologics for inflammatory skin diseases during the COVID‐19 pandemic in our hospital. The observation period was between 1 January 2020 and 23 February 2021. In this study, we enrolled 227 patients with psoriasis, six patients with palmoplantar pustulosis (PPP), 69 patients with atopic dermatitis (AD), and five patients with hidradenitis suppurativa (HS). Bioswitch was performed in 25 patients with psoriasis (11.0%). Biologics were discontinued in 14 patients with psoriasis (6.2%), 10 patients with AD (14.5%), and four patients with HS (80.0%); they were not discontinued in patients with PPP. The introduction of biologics was observed in 27 patients with psoriasis (11.9%), four patients with PPP (66.7%), 33 patients with AD (47.8%), and two patients with HS (40.0%). The use of telephone consultations was observed in four patients with psoriasis and two patients with AD. One patient, who received adalimumab for the treatment of psoriatic arthritis, suffered from COVID‐19 and recovered after a mild course. In conclusion, we report our experience regarding the use of biologic drugs for inflammatory skin diseases. The use of biologics seemed safe for use amidst COVID‐19 infection during the observation period; however, further observation on a larger number of patients is required to confirm the risks and benefits of biologic use in the COVID‐19 era.